Emergence of Filipino ethical consumers: A critical realism research - Cifra, Jose Manuel V. (Animo Repository, 2021)
The purpose of the paper is to identify the causal powers of business ethics to the emergence of ethical consumers in the Philippines. The research will adopt a critical realist research philosophy to explain the phenomenon which builds on the studies of Edwards et al. (2014), McEvoy (2006), Sayer (2000), and Zachariadis (2013). The research will also make use of the Theory of Planned Behavior of Ajzen (1991) and the Responsible Sustainable Consumer Behavior (RSCB) of Hosta and Zabkar (2019) to help advance the perception of the causal relationship between business ethics and the emergence of ethical consumers in the Philippines. This study will utilize primary data through a mixed methodology of a focus group discussion (FGD) and a survey questionnaire with its target respondents being Filipino consumers from the generations Y and Z. A total of four focus group discussions were conducted with questions developed that seek to identify the causal mechanisms and conditions of the emergence of ethical consumers in the Philippines. The researchers also conducted quantitative research through a survey questionnaire constructed based on the responses of the FGD and supporting literature. A Likert scale was utilized to measure their responses to each question. Descriptive statistics are obtained and a multiple regression analysis was conducted using the general linear model to identify the relationship of the causal mechanisms on ethical consumption. Results show that only certain predictors have a causal effect on consumers’ willingness to reward ethical behavior and punish unethical behavior, However, results should be interpreted with caution since the study is not perfectly conclusive to what happens in reality, rather is just a working model that needs to be continuously developed.